In the Era of Genomics, Should Tumor Size Be Reconsidered as a Criterion for Neoadjuvant Chemotherapy?. (20th March 2015) - Pivot, Xavier; Mansi, Laura; Chaigneau, Loic; Montcuquet, Philippe; Thiery-Vuillemin, Antoine; Bazan, Fernando; Dobi, Erion; Sautiere, Jean L.; Rigenbach, Frederic; Algros, Marie P.; Butler, Steve; Jamshidian, Farid; et al.
Abstract: Background: The Oncotype DX recurrence score (RS) assay has been validated for prediction of 10-year risk of distant recurrence and likelihood of benefit from chemotherapy in patients with estrogen receptor (ER)-positive, HER2-negative early breast cancer. Patients with high RS tumors have substantial benefit, and patients with low RS tumors have minimal if any benefit from chemotherapy. Tumor size is used as a key parameter when selecting patients for neoadjuvant chemotherapy. The aim of this study was to assess the distribution of RS in patients selected for neoadjuvant chemotherapy primarily according to tumor size. Patients and Methods: Patients with ER-positive and HER2-negative tumors that were node-negative or had no more than 1 positive node from three trials were included in this study. Oncotype DX was performed at Genomic Health, Inc., blinded to the clinical data. Descriptive statistics were calculated for distribution of RS for all cases. Results: Of 277 patients, 96 met eligibility criteria, and 81 had sufficient material for analysis. Median tumor size was 40 mm (interquartile range [IQR], 30–50 mm). Grade I, II, and III were observed in 13, 49, and 17 cases, respectively. There was a wide distribution of RS with a median of 21.4 (IQR, 16.05-26.75). In total, 23 (28.3%) had high, 28 (34.6%) intermediate, and 30 (37%) low RS results. Conclusion: The RS may provide relevant information for neoadjuvant treatment decisions in select patients both in clinical practice and in studies. Inclusion of low RS disease patients in neoadjuvant trials will likely only dilute the ability to look at treatment effects. Abstract : The aim of this study was to assess the distribution of Oncotype DX recurrence score (RS) in patients selected for neoadjuvant chemotherapy primarily according to tumor size. Neoadjuvant chemotherapy provides limited benefit with no pathological complete response (pCR) observed in patients with low RS results. Inclusion of patients with such tumors in neoadjuvant trials using pCR as an efficacy measure will dilute the ability to look at treatment effects.